UJI EFIKASI INSEKTISIDA PIRETHROID SINTETIK BERBAHAN AKTIF D-ALLETHRIN DAN PERMETHRIN TERHADAP AEDES AEGYPTI DENGAN APLIKASI PENGASAPAN - Suwasono, Hadi; Boesri, Hasan (Jurnal Kedokteran YARSI, 2007)
Aedes aegypti, vector of DHF, control has been relied on insecticides to prevent the disease transmission. Vector resistance will be speeded up by frequent use of insecticides; therefore alternative insecticides should be sought and tested. In this study, an efficacy test of insecticide containing active ingredient of d-allethrin 10% and permethrin 20% against caged Ae. aegypti hang indoor and outdoor was conducted by thermal fogging application.  Both concentrations of 5 ml and 7,5 ml by product per liter diesel oil showed a knockdown effect of about 98 ? 100% in less than 60 minutes. After 24 hours holding period at the laboratory about 98 ? 100% of Ae.aegypti mortality was observed. It was concluded that the insecticide was effective in killing Ae. aegypti.